Modular functionalization and hydrogel formation via red-shifted and self-reporting [2+2] cycloadditions. Issue 6 (24th December 2020) - Ludwanowski, Simon; Hoenders, Daniel; Kalayci, Kubra; Frisch, Hendrik; Barner-Kowollik, Christopher; Walther, Andreas
Abstract : We introduce a modular photodynamic covalent crosslinker, named qStyPy, with an increased water-solubility that undergoes [2+2] cycloadditions upon irradiation with 470 nm and directly self-reports on its cycloadduct formation. Abstract : We present a modularly applicable, red-shifted and self-reporting photodynamic covalent crosslinker, abbreviated qStyPy, that performs [2+2] cycloadditions upon irradiation with 470 nm in water. The rational design of qStyPy increases its hydrophilicity due to a permanent charge and features a broad emission in the far-red/near-infrared regime as a readout for the cycloadduct formation, rendering qStyPy suitable for biomedical applications.